Detection of SARS-CoV-2 Antibodies in Matched Pregnant Women and Newborn Blood - Haytoglu, Zeliha; Haytoglu, Eren; Ozlu, Ferda; Yıldızdas, Hacer Yapıcıoglu; Kibar, Filiz; Çetiner, Salih; Gulası, Selvi; Uysal, Gulsum; Gundeslioglu, Ozlem Ozgur; Alabaz, Derya; Sucu, Mete; Celik, Umit (Journal of Pediatric Infectious Diseases, 2023)
Objective The factors affecting the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies from mother to newborn and the duration of seropositivity rates in these infants have not yet been clearly demonstrated. The objectives of this study were to assess the levels of SARS-CoV-2 spike–specific immunoglobulin G (IgG) in women infected in the pregnancy period and newborns born to these women and to search the transplacental transfer ratio of spike-specific IgG.Methods Seventy pregnant women with symptomatic SARS-CoV-2 infection and their newborns were prospectively followed. Anti–SARS-CoV-2 immunoassay was used for the detection of the in vitro quantitative determination of total antibodies to the SARS-CoV-2 spike protein.Results Spike-specific IgG was demonstrated in 89.1% (44 of 46) of pregnant women infected more than 14 days before delivery and in 92.6% (43 of 44) of their newborns. Median transfer ratio of spike-specific Ig was 0.87 (interquartile range [IQR], 0.34–0.90), 1.0 (IQR, 0.9–0.29), and 0.81 (IQR, 0.02–1.0) in first trimester (n = 4), second trimester (n = 14), and third trimester (n = 28) pregnant women, respectively. Antibody transfer ratio was correlated with time elapsed from infection (p < 0.001). Peak antibody transfer ratio above 1 was observed at a median 60 to 120 days after the infection from delivery. Antibody transfer ratio was high in pregnant women infected more than 60 days before delivery (p < 0.001). Transfer ratio was significantly higher in the severe-critically symptomatic women (n = 15) than the mild-moderately symptomatic women (n = 55) (p = 0.001). At 3 months, 18 of 25 infants (72%) had spike-specific IgG.Conclusion Timing from infection to delivery and severity of maternal infection are critical in assessing the antibody generation and transport. Higher antibody transfer ratio can be detected in neonates when SARS-CoV-2 infection is present for more than 60 days before birth. Maternally derived antibody can persist for 3 months after birth.
Keywords: COVID-19; pregnancy; SARS-CoV-2; spike-specific IgG